"I Don't Wanna Be around Nobody": A Retrospective Interview of Homeless Social Networks. Issue 48 (4th May 2022) - Addo, Reuben; Ivey, Dorothea
Abstract: The importance of social networks to the homeless population cannot be overemphasized. Social networks play an important role in the path toward homelessness and out of homelessness. While previous studies have shown the relationship between social networks and negative health outcomes among the homeless, there is limited literature on how homeless individuals construct their social networks. The purpose of this study is to understand how formerly homeless adults constructed their social networks during homelessness. Drawing on both narrative and thematic analysis methodologies, a sample of previously homeless adults (n = 20) were retrospectively interviewed on their social network experiences while homeless. Data analysis was guided by thematic analysis. Results indicated participants restricted their social networks on the premise of their mistrust of people, mental illness, and self-shame. The study suggests homeless social networks may be constructed based on experiences preceding homelessness and during homelessness. Findings suggest the lack of supportive networks among homeless adults may inform their limited social interactions. Thus, interventions to increase homeless social networks may improve overall wellbeing and enhance community reintegration efforts. Future research should further explore how homeless individuals' social networks are constructed in other contexts.